1997
DOI: 10.1090/s0894-0347-97-00240-3
|View full text |Cite
|
Sign up to set email alerts
|

Infinitesimal 1-parameter subgroups and cohomology

Abstract: This is the first of two papers in which we determine the spectrum of the cohomology algebra of infinitesimal group schemes over a field k of characteristic p > 0. Whereas [SFB] is concerned with detection of cohomology classes, the present paper introduces the graded algebra k[V r (G)] of functions on the scheme of infinitesimal 1-parameter subgroups of height ≤ r on an affine group scheme G and demonstrates that this algebra is essentially a retract ofThis work is a continuation of [F-S] in which the exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
171
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(174 citation statements)
references
References 9 publications
3
171
0
Order By: Relevance
“…[19]). In the work of Suslin, Friedlander, and the author [29,30] it was shown that the family of subgroup schemes {G a(r) } plays the role of elementary abelian subgroups in detecting projectivity and nilpotence of cohomology for infinitesimal group schemes. Specifically, [30, [30, proposition 7•6] is an analogue of Chouinard's theorem (Theorem 1•3) about detecting projectivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19]). In the work of Suslin, Friedlander, and the author [29,30] it was shown that the family of subgroup schemes {G a(r) } plays the role of elementary abelian subgroups in detecting projectivity and nilpotence of cohomology for infinitesimal group schemes. Specifically, [30, [30, proposition 7•6] is an analogue of Chouinard's theorem (Theorem 1•3) about detecting projectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Within the literature, it has been noted that it is often more convenient to work instead with prime ideals, while maintaining the traditional terminology. This study of cohomology via varieties was extended to restricted Lie algebras by Friedlander and Parshall [15,16], as well as by Jantzen [20], and later to arbitrary infinitesimal group schemes by Suslin, Friedlander, and the author [29,30]. Here the detection properties of the family of subgroup schemes {G a(r) } was crucial for identifying the varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Since V(U)V(G) (cf. [, (1.5)]), the first part of the proof implies that imα(ur1)M=V for every {1,,p1}. This shows that the scriptG‐module M has the equal images property.…”
Section: Modules For Finite Group Schemesmentioning
confidence: 75%
“…General theory then shows that Vfalse(scriptGfalse)=prefixHom Hopf false(kGafalse(rfalse),kscriptGfalse)prefixHomkfalse(kGafalse(rfalse),kscriptGfalse):=Mis an affine variety. In fact, V(G) is the variety of k‐rational points of the scheme of infinitesimal one‐parameter subgroups introduced in .…”
Section: Modules For Infinitesimal Group Schemes and Maps To Grassmanmentioning
confidence: 99%
“…The previous results for p-restricted Lie algebras were extended to infinitesimal group schemes in two papers by A. Suslin, C. Bendel, and the author [30] in 1997. Infinitesimal group schemes are group schemes whose coordinate algebras are finite dimensional, local k-algebras; infinitesimal group schemes of height 1 correspond naturally to p-restricted Lie algebras (see [23]).…”
Section: Extensions and Refinementsmentioning
confidence: 95%